The Relationship of Orofacial Pain and Dental Health Status and Oral Health Behaviours in Facial Burn Patients. (8th May 2021) - Chaudhary, Farooq Ahmad; Ahmad, Basaruddin; Javed, Muhammad Qasim; Yakub, Shaikh Shoeb; Arjumand, Bilal; Khan, Asma Munir; Mustafa, Saeed
Abstract : This study aims to examine the association of orofacial pain and oral health status and oral health behaviours in facial burn patients. The participants in this cross-sectional study were randomly recruited from the Burn Care Center, Institute of Medical Sciences, Islamabad, Pakistan. An intraoral evaluation was carried out to record the DMFT and OHI-S. A self-administered questionnaire was used to collect information on sociodemographic status, brushing frequency, and dental visits. Orofacial pain during mandibular movement was assessed using the Visual Analogue Scale (VAS). Psychological status was assessed using the Generalized Anxiety Disorder Scale and Impact of Events Scale. ANOVA and simple and multiple linear regression tests were used to analyse the data. From the 90 facial burn patients included, the majority were below 34 years of age, female, single or divorced, and unemployed. The mean DMFT was 10.7, and 71% had poor oral hygiene. 56% of the participants had moderate-to-severe anxiety, and 68% had posttraumatic stress disorder. 53% of the participants had moderate-to-severe pain during mouth opening or moving the mandible with a mean score of 41.5. Analyses showed that orofacial pain was associated with less frequent brushing, irregular dental visits, greater DMFT score, and more plaque accumulation (OHI-S). It was also associated with employment status, the severity of a burn, anxiety, and stress. The treatment and management of dental and oral conditions in burn patients need judicious balance in controlling and accurate assessment of the pain and improving psychological problems in burn patients.